A finite element simulation for carburizing heat treatment of automotive gear ring incorporating transformation plasticity. (5th June 2016) - Kim, Dong-Wan; Cho, Hoon-Hwe; Lee, Won-Beom; Cho, Kyun Taek; Cho, Yi-Gil; Kim, Se-Jong; Han, Heung Nam
Abstract: A finite element model was developed to predict the deformation, temperature history, carbon diffusion, phase fraction, and hardness during the carburizing heat treatment of automotive annulus gear ring, initially made of a medium carbon steel. Carburizing gas with a constant carbon potential for entire surfaces of the gear was assumed. The temperature and pressure driven carbon diffusion was solved by the finite element simulation based on Fick's law. Both the diffusional and displacive phase transformations during the heat treatment were modeled incorporating the carbon concentration inside the gear. The constitutive equation of the transformation plasticity was incorporated into the finite element model. Strains due to the phase transformation, transformation plasticity, and thermal expansion/contraction were calculated by the finite element model. The prediction accuracy for the phase evolution, hardness distribution, and dimensional change of the gear ring was verified with the measurement data. Graphical abstract: Highlights: Numerical model is developed to predict deformation, temperature, carbon diffusion, and transformation during carburization. The profiles of carbon concentration are calculated by the finite element simulation based on Fick's law. Transformation plasticity plays an important role in unexpected dimensional instability in industrial applications. Hardness of the gear is well predicted considering the carbon concentration and phase fraction.